2019
DOI: 10.1080/10942912.2019.1573831
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of sulfated polysaccharides from Gracilaria gracilis and Ulva lactuca and their radical scavenging, metal chelating, and cholinesterase inhibitory activities

Abstract: This study was designed to evaluate the antioxidant and cholinesterase inhibitory activities of sulfated polysaccharides from Gracilaria gracilis (PGCL) and Ulva lactuca (PULV). PGCL and PULV were extracted and characterized with Scanning electron microscope-energy dispersive x-ray (SEM-EDX), Fourier transform infrared spectroscopy (FTIR) and Gas chromatography-mass spectroscopy (GC-MS). The radical (2,2-azinobis-3-ethylbenzothiazoline-6-sulfonate [ABTS] 2,2-diphenyl-1-picrylhydrazyl [DPPH], and hydroxyl [OH])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 42 publications
7
40
0
Order By: Relevance
“…Interestingly, it exhibited peculiar chemical characteristics, such as high uronic acid and sulfate contents, and importantly specific functional units, such as carboxymethyl, methoxyl, Journal of Chemistry and sulfated groups. Sulfated and/or carboxymethylated EPS have attracted attention in the field of pharmacology for their valuable biological activities [30,33,34]. Moreover, carboxymethylation and sulfation were applied to chemically modify polysaccharides for enhancing their bioactivities [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it exhibited peculiar chemical characteristics, such as high uronic acid and sulfate contents, and importantly specific functional units, such as carboxymethyl, methoxyl, Journal of Chemistry and sulfated groups. Sulfated and/or carboxymethylated EPS have attracted attention in the field of pharmacology for their valuable biological activities [30,33,34]. Moreover, carboxymethylation and sulfation were applied to chemically modify polysaccharides for enhancing their bioactivities [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effect of some algal polysaccharides on Zn-induced neuronal damage in hippocampal cells was investigated. These polysaccharides have been fully characterized in our previous study and were tentatively identified as fucoidan (PKPM), ulvans (PULV and PULT), and carrageenan (PGCL and PMNP) [19,20]. The presence of sulfate moiety was confirmed in these polysaccharides including monosaccharides such as fucose, rhamnose, glucose, mannose, galactose, xylose, and allose.…”
Section: Discussionmentioning
confidence: 77%
“…The extraction of the sulfated polysaccharides from E. maxima (PKPM), G. pristoides (PMNP), U. rigida (PURL), U lactuca (PULV) and G. gracilis (PGCL) was done as previously described [19,20]. Each seaweed was dried at 25°C and was ground into powder using a blender, after which they were de-pigmented in different flasks with 400 mL of hexane.…”
Section: Extraction Of Sulfated Polysaccharidesmentioning
confidence: 99%
“…Interestingly, compounds 37-39 and 48 were all isolated and characterized from the alga C. fragile and following this study, it was suggested that sterol compounds may prove to be useful biomarkers for this genus allowing for easier taxonomic distinction between other members of the Codiaceae family [44,45]. Much of the literature available for the genus Ulva involves biological activity studies on polysaccharides [46][47][48][49], many of the sterols found within this genus have shown promising in vitro bioactivity. In particular, the glycosidic sterol (47) from U. lactuca has been shown to be an effective anti-bacterial, anti-fungal and anti-inflammatory agent in vitro [41].…”
Section: Steroids/sterolsmentioning
confidence: 73%
“…The sterols (see supporting information Figure S5) of U. lactuca (30-36, 40, 47) and U. australis (40,41,42,(44)(45)(46) have been studied extensively [39][40][41][42][43]. Many of the sterols found in the green algae of Port Phillip Bay appear to have a C-19 core skeleton with differing functionalities of the side chain.…”
Section: Steroids/sterolsmentioning
confidence: 99%